1996
DOI: 10.1212/wnl.47.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of nigrostriatal denervation and L-dopa therapy on the expression of glutamic acid decarboxylase messenger RNA in the pallidum

Abstract: To examine the consequences of nigrostriatal denervation and L-dopa treatment on the basal ganglia output system, we analyzed, by quantitative in situ hybridization, the messenger RNA coding for glutamic acid decarboxylase (Mr 67,000) (GAD67 mRNA) in pallidal cells from patients with Parkinson's disease (PD), monkeys rendered parkinsonian by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) receiving or not receiving L-dopa, and their respective control subjects. In MPTP-treated monkeys, the expression of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 10 publications
10
53
0
Order By: Relevance
“…Thus, 3 days after last L-DOPA dose, GAD 67 levels were increased in the striatum and GP when dyskinetic rats were compared with nondyskinetic 6-OHDAlesioned animals and control nonlesioned rats (Cenci et al, 1998). In contrast, in the dyskinetic macaque killed 24 hours after last dose of L-DOPA and in L-DOPA-treated PD patients, GAD 67 mRNA levels within the GP were not different from those encountered in nonparkinsonian animals and subjects (Herrero et al, 1996). In the striatum of the MPTPlesioned macaque killed in the off-state, GAD 67 mRNA levels were increased and remained increased following chronic L-DOPA therapy and induction of dyskinesia compared with nonparkinsonian macaques (Levy et al, 1995a); in PD patients chronically treated with L-DOPA, GAD 67 mRNA levels were reduced in the striatum compared with healthy control subjects (Levy et al, 1995a).…”
Section: The Gabaergic Systemmentioning
confidence: 76%
“…Thus, 3 days after last L-DOPA dose, GAD 67 levels were increased in the striatum and GP when dyskinetic rats were compared with nondyskinetic 6-OHDAlesioned animals and control nonlesioned rats (Cenci et al, 1998). In contrast, in the dyskinetic macaque killed 24 hours after last dose of L-DOPA and in L-DOPA-treated PD patients, GAD 67 mRNA levels within the GP were not different from those encountered in nonparkinsonian animals and subjects (Herrero et al, 1996). In the striatum of the MPTPlesioned macaque killed in the off-state, GAD 67 mRNA levels were increased and remained increased following chronic L-DOPA therapy and induction of dyskinesia compared with nonparkinsonian macaques (Levy et al, 1995a); in PD patients chronically treated with L-DOPA, GAD 67 mRNA levels were reduced in the striatum compared with healthy control subjects (Levy et al, 1995a).…”
Section: The Gabaergic Systemmentioning
confidence: 76%
“…The functional state of the GPe in the parkinsonian state has been a matter of discussion 106,107 (see the Table). Studies have reported a low firing rate in the GPe of parkinsonian animals, 108 no change, 109 or slight increase at the time of onset of parkinsonian signs.…”
Section: Globus Pallidus Pars Externa-subthalamic Nucleus-globus Pallmentioning
confidence: 99%
“…104 Third, the model predicts that the GPe is hypoactive but this finding has not been confirmed. 105,106 Finally, a large number of pathways that may have a crucial role in the normal and pathologic functioning of the circuit are not considered in the model, eg, the pallidopallidal projection, 107 the dopaminergic innervation of the STN 24 and globus pallidus, 21 the afferent projections from the parafascicular nucleus and the pedunculopontine nucleus to the STN, 108 and the projections that form the pedunculopontine nucleus to the basal ganglia.…”
Section: Dopaminergic Control Is a Fourthmentioning
confidence: 99%